Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Fast-ice distribution in East Antarctica during 1997 and 1999 determined using RADARSAT data - Giles, A Barry; Massom, Robert A; Lytle, Victoria I (Journal of Geophysical Research: Oceans, 2008)
We present the first detailed maps of fast ice around East Antarctica (75°E–170°E), using an image correlation technique applied to RADARSAT ScanSAR images from November in 1997 and 1999. This method is based upon searching for, and distinguishing, correlated regions of the ice-covered ocean which remain stationary, in contrast to adjacent moving pack ice. Within the overlapping longitudinal range of ∼86°E–150.6°E, the total fast-ice area is 141,450 km2 in 1997 and 152,216 km2 in 1999. Calibrated radar backscatter data are also used to determine the distribution of two fast-ice classes based on their surface roughness characteristics. These are “smooth” fast ice (−25.4 dB to −13.5 dB) and “rough” fast ice (−13.5 dB to −2.5 dB). The former comprises ∼67% of the total area, with rough fast ice making up the remaining ∼33%. An estimate is made of fast-ice volume, on the basis of fast-ice type as a proxy measure of ice thickness and area. Results suggest that although fast ice forms 2–16% of the total November sea ice area for this sector of East Antarctica in 1997 and 1999 (average 8.3% across maps), it may comprise 6–57% of the total ice volume (average ∼28% across maps). Grounded icebergs play a key role in fast-ice distribution in all regions apart from 150°E–170°E. These are “snapshot” estimates only, and more work is required to determine longer-term spatiotemporal variability.
Keywords: Sørishavet; batymetri; biologi; havis; kartlegging; landfast is; satellite bilder; sjøis; økologi

Halo of ice deformation observed over the Maud Rise seamount - Lindsay, Ronald; Kwok, Ronald; de Steur, Laura; Meier, Walt (Geophysical Research Letters, 2008)
A distinctive halo of sea ice deformation was observed above the Maud Rise seamount in the eastern Weddell Sea in the winter of 2005. The deformation halo is coincident with a halo of low mean ice concentration that is often observed in the region. Monthly mean ice vorticity estimates for the months July through November reveal the deformation zone most clearly in an arc about 100 km northwest of the seamount where there is a strong gradient in the bathymetry at depths of 3000–5000 m. The deformation was computed from satellite-based ice motion vectors derived from Envisat Synthetic Aperture Radar backscatter images. The deformation halo is evidence of a Taylor cap circulation over the seamount, which has been described and analyzed with modeling studies and concurrent oceanographic observations obtained during an extensive field campaign.
Keywords: Sørishavet; Weddellhavet; havis; havstrømmer; hydrografi; oseanografi; sjøis; vannvirvler